Effects of Emerging Market Asset Purchase Program Announcements on Financial Markets During the COVID-19 Pandemic - Sever, Can (IMF Working Papers; Working Paper ;, 2020)
The COVID-19 pandemic led many emerging market central banks to adopt, for the first time, unconventional policies in the form of asset purchase programs. In this study, we analyze the effects of these announcements on domestic financial markets using both event studies and local projections methodology. We find that these asset purchase announcements lowered bond yields, did not lead to a depreciation of domestic currencies, and did not have much effect on equities. While the immediate effect of asset purchases appears positive, further consideration of the risks and longer-term effects of unconventional monetary policies is needed. We highlight the trade-offs involved with the implementation of these measures, and discuss their risks. This working paper adds to the debate on how asset purchase programs should be a regular part of the emerging market policy toolkit.